Microbiome and Metabolome Analyses of Milk From Dairy Cows With Subclinical Streptococcus agalactiae Mastitis—Potential Biomarkers - Tong, Jinjin; Zhang, Hua; Zhang, Yonghong; Xiong, Benhai; Jiang, Linshu (Frontiers in Microbiology, 2019)
The objective of the present study was to investigate the potential biomarkers for milk microbiota diversity and metabolite profiles of healthy dairy cows compared to those with subclinical Streptococcus agalactiae mastitis and to establish correlations between the milk microbiota and metabolic factors. Six milk samples from cows with subclinical S. agalactiae mastitis (GBS) and six from healthy cows (CON) were analyzed for microbial populations using16S rRNA gene sequences from Miseq high-throughput sequencing and for milk metabolites by gas chromatograph-time-of-flight mass spectrometry (GC-TOFMS). Both PCA and OPLS-DA indicated that metabolites were well-separated from each other in milk samples form the two groups. Infection with S. agalactiae dramatically altered microbial diversity and the GBS group had significantly fewer Proteobacteria, Actinobacteria and Acidobacteria, with increased abundance of Firmicutes (p<0.01). Several bacterial genera were significantly more abundant in milk samples from the GBS group than the healthy group, such as Streptococcus, and there was a tendency to increase in Turicibacter (p = 0.07) and Enterococcus spp (p = 0.07). Five milk metabolites were significantly higher in the GBS group: phenylpyruvic acid, the ratio of homogentisic acid to 4-hydroxyphenylpyruvic acid, the ratio of xanthine to guanine, uridine and glycerol. The enrichment of specific metabolites indicated that galactose metabolism, pentose and glucuronate interconversions, starch and sucrose metabolism, alanine, aspartate and glutamate metabolism, arginine biosynthesis, citrate cycle (TCA cycle), D-glutamine and D-glutamate metabolism, neomycin, kanamycin and gentamicin biosynthesis. Several typical metabolites were highly correlated with specific ruminal bacteria, such as Streptococcaceae, Lachnospiraceae, Lactobacillaceae and Corynebacteriaceae, which demonstrated the functional correlation between the milk microbiome and associated metabolites. These findings revealed that milk microbiota and metabolite profiles were significantly different between the two groups of cows, leading to the question whether the microbiota associated with the bovine mammary gland could be related to mammary gland health. There was also a relationship between milk quality and presence of spoilage bacteria. Other bacterial taxa should be investigated as such studies may provide insights into how perturbations of the milk metabolomic profile relate to the differences in milk synthesis between healthy cows and those with subclinical mastitis.